THE ROLE OF ORNITHODOROS TICKS IN AFRICAN SWINE FEVER EPIDEMIOLOGY (SURVEY) - A. S. Pershin; S. G. Remyga; I. V. Shevchenko; A. A. Shevtsov; N. N. Vlasova; A. S. Igolkin (Ветеринария сегодня, 2018)
The paper summarizes the data on biological characteristics of argasid ticks, their involvement in ASF epidemiology in Europe and Russian Federation. Infectious diseases transmission by tick bites is a serious medical and veterinary problem. Viral replication in ticks is one of the factors contributing to formulation of ASF virus populations with different levels of glycosylation. Isolates recovered from ticks are characterized by genome changes in the form of DNA point mutations. Natural virus passages in ticks may lead to emergence of new variants of the virus.